(untitled) (Biodiversitas Journal of Biological Diversity, 2006)
Indonesian tropical climate have an opportunity for fungi growth as Aspergillus flavus Link which can produce aflatoxin within foodstuffs, include condiment of fermented shrimp. Aflatoxin B1 is the dangerous agent having roles as carcinogenic, mutagenic and teratogenic. The aims of this research were known kinds of moulds and detection of aflatoxin B1 on commercial condiments fermented of shrimp. Two brands of commercial condiments fermented of shrimp were taken from traditional markets and supermarkets in Surakarta. Isolation was done by made suspension of sample in aquadets. Suspension on appropriate dilutions was grown on CDA (Czapek’s Dox Agar) media with surface spread. The grown colonies were separated and grown on PDA (Potato Dextrose Agar) slant media. Furthermore, isolates were cultured on CDA and MEA (Malt Extract Agar) media. The grown colonies were microscopes and microscopes examined and identified. Existence of aflatoxin B1 was known by Commercial RIDA Screen ELISA Kit that could detect qualitatively and quantitatively with detection sensitive < 1.7 ppb. Moulds that could be isolated from condiments fermented of shrimp were: Aspergillus flavus Link, Aspergillus niger van Tieghem, Aspergillus wentii Wehmer, Aspergillus PU1 or Aspergillus PU2 and Penicillium citrinum Thom. There was aflatoxin B1 contaminated to 2 brands of commercial condiments fermented of shrimp that were examined. Traditional markets’ commercial condiments fermented of shrimp contained higher aflatoxin B1 than supermarkets’. The brands of commercial condiment of fermented shrimp which had better inner package quality contained lower aflatoxin B1 than the worst inner package quality of commercial condiments of fermented of shrimp. © 2006 Jurusan Biologi FMIPA UNS Surakarta Keywords: commercial condiments fermented of shrimp, moulds, aflatoxin B1